Resensi Buku: Autism and Worship: A Liturgical Theology - Lim, Budianto (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2025)
Armand Leon Van Ommen has written a book about autism and worship. This is an academic work in the area of liturgical theology. He brings readers to consider how the presence of autistic people in worship influence the way we design and execute liturgy. The ultimate purpose is to develop a liturgical theology of availability and participation as an ecclesiological praxis that truly highlight the essence of the identity of believers.